Auroral ionospheric F region density cavity formation and evolution: MICA campaign results. Issue 4 (17th April 2014) - Zettergren, M.; Lynch, K.; Hampton, D.; Nicolls, M.; Wright, B.; Conde, M.; Moen, J.; Lessard, M.; Miceli, R.; Powell, S.
<x xml:space="preserve">Abstract</x> Auroral ionospheric F region density depletions observed by PFISR (Poker Flat Incoherent Scatter Radar) during the MICA (Magnetosphere‐Ionosphere Coupling in the Alfvén Resonator) sounding rocket campaign are critically examined alongside complementary numerical simulations. Particular processes of interest include cavity formation due to intense frictional heating and Pedersen drifts, evolution in the presence of structured precipitation, and refilling due to impact ionization and downflows. Our analysis uses an ionospheric fluid model which solves conservation of mass, momentum, and energy equations for all major ionospheric species. These fluid equations are coupled to an electrostatic current continuity equation to self‐consistently describe auroral electric fields. Energetic electron precipitation inputs for the model are specified by inverting optical data, and electric field boundary conditions are obtained from direct PFISR measurements. Thus, the model is driven in as realistic a manner as possible. Both incoherent scatter radar (ISR) data and simulations indicate that the conversion of the F region plasma to molecular ions and subsequent recombination is the dominant process contributing to the formation of the observed cavities, all of which occur in conjunction with electric fields exceeding ∼90 mV/m. Furthermore, the cavities often persist several minutes past the point when the frictional heating stops. Impact ionization and field‐aligned plasma flows modulate the cavity depth in a significant way but are of secondary importance to the molecular generation process. Informal comparisons of the ISR density and temperature fits to the model verify that the simulations reproduce most of the observed cavity features to a reasonable level of detail.